The study of periodicity of eating & public health nutrition issues - Harrington, Karen E. (Trinity College (Dublin, Ireland). School of Medicine. Discipline of Clinical Medicine, 2001)
This thesis set out to provide an objective understanding of periodicity of eating in a group of free- living adults, by determining the temporal pattern of nutrient intake during eating occasions throughout the day. A dietary assessment study was carried out using a 7-day estimated food diary in a sample of 133 adults recruited from a city local authority. During the survey period, respondents were met on at least three occasions to encourage and motivate them to follow their usual dietary habits and to record their intakes in as detailed a manner as possible. A combination of quantification methods was used to obtain best estimates for the weights of all food and drink consumed, including a photographic food atlas, manufacturers' information, the weighing of specific food and drinks, household measures and standard portion sizes. The food and drink information was coded to allow analysis of the data in terms of individual eating occasions. An eating occasion was coded to the nearest hour and included every item of food and drink consumed within an hourly period. Nutrient analysis was carried out using the FOODBASE® program on each eating occasion of each of the seven days for each respondent. This program was specifically chosen as it allowed specification of the amount and type of fat used in preparing and cooking foods. The nutrient intake data was entered into SPSS® to create a database, which contained every hour of each of the seven days for each respondent, together with the nutrient analysis data of every eating occasion, at the specific hour of consumption. This database was then used to determine the temporal pattern of nutrient intake during eating occasions throughout the day to address a number of questions. Eating occasions of non-nutritive value were not included in the analysis.
Keywords: Clinical Medicine, Ph.D.; Ph.D. Trinity College Dublin